Randomizable Proofs and Delegatable Anonymous Credentials - Belenkiy, Mira; Camenisch, Jan; Chase, Melissa; Kohlweiss, Markulf; Lysyanskaya, Anna; Shacham, Hovav (CRYPTO 2009, 2008)
We construct an efficient delegatable anonymous credentials system. Users can anonymously and unlinkably obtain credentials from any authority, delegate their credentials to other users, and prove possession of a credential L levels away from a given authority. The size of the proof (and time to compute it) is O(Lk), where k is the security parameter. The only other construction of delegatable anonymous credentials (Chase and Lysyanskaya, Crypto 2006) relies on general non-interactive proofs for NP-complete languages of size k ¿(2 L ). We revise the entire approach to constructing anonymous credentials and identify randomizable zero-knowledge proof of knowledge systems as the key building block. We formally define the notion of randomizable non-interactive zero-knowledge proofs, and give the first instance of controlled rerandomization of non-interactive zero-knowledge proofs by a third-party. Our construction uses Groth-Sahai proofs (Eurocrypt 2008).